(untitled) (Bioscience Journal, 2018)
The aging process is something that occurs naturally during the lifetime of the human being. It causes biological, psychological and social changes in the body. Anthropometry, which until the late nineteenth century was a common tool in clinical and taxonomic practices, has gained great importance as a public health measure. This methodology is also important in the evaluation of morbidities in individuals and their social practices. Thus, the objective of the present study was to evaluate facial shape characteristics in the elderly, associated with chronic diseases such as diabetes and hypertension, based on two-dimensional images of the lateral and frontal views of the face. Analysis of discriminant function and cross validation presented significant differences (p<0.01), for sexual dimorphism in both views and the presence and/or absence of diabetes and hypertension (p<0.01). For the male sex, the highest classifications were related to the complete lateral and frontal views, in 75.2% and 81.2% of cases, respectively. In terms of the female sex, they referred to the frontal view without the orolabial region or jaw (71.4%). There was variation in the facial bilateral symmetry in the elderly, with the presence of fluctuating and directional asymmetry (p<0.01). Despite morphological variations associated with aging, it is possible to use geometric morphometrics techniques to observe characteristics in facial shape related to the presence of diabetes, hypertension, and the presence or absence of both diseases.